2020
DOI: 10.1177/0897190020958263
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Advanced Pharmacy Practice Experience Characteristics on Postgraduate Year 1 Residency Match Rates

Abstract: Background: Mentors often provide advice to students regarding selection of Advanced Pharmacy Practice Experience (APPE) rotations to strengthen their candidacy for a residency position. However, the impact of APPE characteristics on the chances of matching is unknown. Objective: To determine the impact of APPE characteristics on Post Graduate Year-1 (PGY1) residency match rates at a Midwest US college of pharmacy. Methods: Graduates from a single college of pharmacy who participated in the PGY1 match in 2015 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…After the full‐text review, a total of 28 studies were identified for inclusion, data extraction, and further analysis (Figure 1). 8‐35 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After the full‐text review, a total of 28 studies were identified for inclusion, data extraction, and further analysis (Figure 1). 8‐35 …”
Section: Resultsmentioning
confidence: 99%
“…Because of the heterogeneity in study methodology and outcomes, the authors only extracted and described factors from the study data that could potentially have an impact on residency match rates. More than half of the studies (Table 1) identified an intervention, types of required or extracurricular activities, or student determination within a pharmacy school that was associated with residency matching 8‐23 . A small number of studies (Table 2) surveyed RPDs regarding their perceptions of desired characteristics of residency candidates 24,25 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations